Analysis of the Contribution of Coastal Women's Business to Household Income (Case Study in Tadang Palie Village, Cempa District, Pinrang Regency) - Nurdiana, Nurdiana; Made, Sutinah; Cangara, Arie Syahruni; Baso, Aris; Gosari, Benny Audy Jaya (PONGGAWA : Journal of Fisheries Socio-Economic, 2021)
Coastal communities have different characteristics from other communities so that they must have different strategies to meet their needs. With the development of technology and the demands of the family economy, women have also contributed to the household economy such as coastal women in Tadang Palie Village. In increasing household income, coastal women in Tadang Palie Village run a business as an effort to help the family economy which aims to fulfill the family's economic needs and develop their potential. The purpose of this study was to determine the types of coastal women's businesses, the income earned by coastal women who have businesses, and the contribution of coastal women's businesses to household income in Tadang Palie Village, Cempa District, Pinrang Regency. As for the determination of respondents using cluster sampling technique which is distinguished by type of business as many as 37 people. The data analysis uses the household income formula and the income contribution of coastal women. Data collection techniques are observation, distribution of questionnaires and interviews. This research was conducted in Tadang Palie Village, Cempa District, Pinrang Regency in January - February 2021. From the results of the study found several types of coastal women's businesses, namely mixed trading businesses, businesses selling dried fish, cake selling businesses, culinary tourism businesses, sewing businesses, a business selling contemporary drinks, and a business selling clothes. Of all the types of coastal women's businesses in Tadang Palie Village, the culinary tourism business has the largest contribution, and the business of selling dried fish has the smallest contribution to household income.